Contemporary Issues in Women's Health. Issue 1 (1st September 2019) - Geary, Michael; Chibwesha, Carla J.; Stringer, Elizabeth
Abstract : Placental growth factor testing for suspected pre‐eclampsia HPV Vaccination: A global public health priority Echo trial shows no increased risk of HIV acquisition with hormonal contraception